2011
DOI: 10.1007/s00445-011-0550-4
|View full text |Cite
|
Sign up to set email alerts
|

A water flow model of the active crater lake at Aso volcano, Japan: fluctuations of magmatic gas and groundwater fluxes from the underlying hydrothermal system

Abstract: The first crater of Nakadake, peak of Aso volcano, Japan, contains a hot water lake that shows interesting variations in water level and temperature. These variations were discovered by precise, continuous observations of the lake independent of precipitation. We developed a numerical model of a hot crater lake and compared with observational data for the period from July 2006 to January 2009. The numerical model revealed seasonal changes in mass flux (75-132 kg/s) and enthalpy (1,840-3,030 kJ/kg) for the flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…The occurrence of an impermeable layer may explain the existence of volcanic lakes. Indeed, magnetotelluric surveys [Kanda et al, 2008] detected a layer of hydrothermal alteration at 100À200 m beneath the floor of Yudamari, a hot crater lake at Aso volcano, Japan [Terada et al, 2012;Shinohara et al, 2015], which may act as an impermeable layer. However, it is plausible that past volcanic explosions repeatedly destroyed the crater floor, including the underlying impermeable alteration layer, and replaced it with fresh eruption material.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of an impermeable layer may explain the existence of volcanic lakes. Indeed, magnetotelluric surveys [Kanda et al, 2008] detected a layer of hydrothermal alteration at 100À200 m beneath the floor of Yudamari, a hot crater lake at Aso volcano, Japan [Terada et al, 2012;Shinohara et al, 2015], which may act as an impermeable layer. However, it is plausible that past volcanic explosions repeatedly destroyed the crater floor, including the underlying impermeable alteration layer, and replaced it with fresh eruption material.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is likely that the apparent temperature of the lake surface in the right bottom side of the lake on the image (47-48 °C) is closest to the actual water temperature. Given that the IR thermometry gives systematically lower values than direct measurements from a buoy by 8.3 °C, which is empirically confirmed by Terada et al (2012), and assuming the skin effect (slight decrease in water temperature in a boundary layer at the very surface of the lake; Oppenheimer 1997) as 2 °C (Terada et al 2008), the real water temperature on that day is estimated to be 53-54 °C. Besides the zonal distribution, we recognize several hot spots in the central part of the lake.…”
Section: Applications To Tir Imagerymentioning
confidence: 94%
“…Undulation due to the steam filaments mentioned above does not account for these hot spots, since it is confirmed that these spots are stable regardless of additional compositing. We consider that these hot spots correspond to the upwelling of high-temperature water or steam that has been envisaged based on the heat and water balance of Yudamari by Terada et al (2012). The image processing of the present study can contribute to the detection of such spot-like temperature anomalies also for other crater lakes.…”
Section: Applications To Tir Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…Terada et al (2012) showed that changes in the shallow hydrothermal system can be tracked by monitoring enthalpy and mass flux to the crater lake. It is also desirable to monitor subsurface electrical resistivity, which is sensitive to the pore fluid/magma conductivity (e.g., Hermance 1995;Gaillard 2004).…”
Section: Aso Volcanomentioning
confidence: 99%